Cognitive costs and gait parameters during single- and dual-task conditions: A comparative study in individuals with and without non-specific neck pain - Ibrahim M. Moustafa; Shorouk Abu-Ghosh; Amal Ahbouch; Shima Abdollah Mohammad Zadeh; Meeyoung Kim; Iman Khowailed (PLoS ONE, 2025)
Background Non-specific neck pain (NSNP) is increasingly common among students, often due to long hours of sitting and frequent use of electronic devices. This widespread issue underscores the importance of understanding how NSNP affects students’ cognitive abilities and motor functions. This study aims to evaluate the effects of NSNP on dual-task performance by analyzing the gait parameters and cognitive performance during both single-task and dual-task conditions. Methods Forty-five participants with NSNP and forty-five age-matched controls were assessed using an optical motion-capture system. Participants underwent gait assessments during both single-task (without cognitive load) and dual-task conditions, in which the cognitive tasks involved simple mathematical computations. Results Results revealed that under single-task conditions, differences in gait parameters between groups were not statistically significant. However, under dual-task conditions, participants with NSNP exhibited significant impairments in gait parameters and higher cognitive costs (p < 0.05). Correlation analysis indicated that pain intensity was significantly associated with cognitive cost and gait parameter alterations during dual-task conditions (p < 0.05). Conclusions These findings suggest that NSNP significantly elevates the cognitive effort required during the dual-task. These findings emphasize the need for interventions to alleviate neck pain and improve both physical and cognitive health.